Results of treatment of painful vertebral fractures by kyphoplasty or conservative symptomatic management: a prospective nonrandomized controlled study: Rezultati zdravljenja bolečih vretenčnih zlomov: prospektivna, ne-randomizirana primerjava med kifoplastiko in simptomatskim zdravljenjem - Strahovnik, Andrej; Fokter, Samo K. (Acta Medico-Biotechnica, 2021)
Purpose: This nonrandomised study analyzed the results of treatment of painful vertebral fractures in patients with primary osteoporosis with balloon kyphoplasty and compared them with conventional management (control group).Methods: Consecutive patients were enrolled from an outpatient orthopaedic department over a four month period. Eight patients were treated with balloon kyphoplasty and eight with a symptomatic approach (analgesics, bed rest, thoracolumbosacral orthosis). Outcome measures included back pain severity measured on a visual analog scale (VAS), activity level measured on a VAS, bed rest, the SF-36 medical outcomes survey, subject satisfaction, and radiomorphology.Results: Patients reported severe back pain interfering with daily activities before treatment. Physical functioning and quality of life were also markedly impaired. Statistically significant (P < 0.05) improvements in pain and functional outcomes occurred after treatment in the kyphoplasty group. Minor improvements were noted in the control group. Clinical outcomes were significantly different between the groups (P < 0.05). Kyphoplasty increased the midline vertebral height of the treated vertebral bodies, whereas in the control group vertebral height decreased. Conclusion: A positive effect of kyphoplasty over conventional treatment was observed on vertebral morphology and patient satisfaction, pain, level of activity, and overall health perception.
Keywords: osteoporosis; vertebral fracture; kyphoplasty; pain; mobility